Liposomal bupivacaine versus standard periarticular injections in total hip and knee arthroplasty: a prospective, randomized non-inferiority trial - Bowen Joseph; Rainey Joshua P.; Linthicum Jonathan; Blackburn Brenna E.; Anderson Lucas A. (SICOT-J)
Introduction: Numerous multimodal pain protocols have been developed to optimize pain control, reduce narcotics consumption, and shorten the length of stay after total hip and knee arthroplasty (THA/TKA). Liposomal bupivacaine (LB) has been postulated to reduce narcotic requirements after arthroplasty but is not without additional cost. The aim of this study was to determine if the addition of LB to our standard periarticular injection would improve postoperative pain and shorten the length of stay in patients undergoing TKA or THA. Methods: We performed a prospective randomized, blinded non-inferiority study of patients undergoing THA and TKA. Patients were randomized to a periarticular injection with and without LB. There were 118 hips and 64 knees included in the study with no demographic differences between groups. Post-operative pain management was performed by a second provider who was blinded to the patient’s experimental group designation. Results: Cost analysis determined that LB increased cost by $305 dollars per patient when accounting for the cost of injections as well as intravenous and oral pain medications. LB led to a minor reduction in narcotic use in THA patients (equivalent to a single 10 mg oxycodone dose), but this difference may lack clinical relevance. No significant benefits were observed in TKA patients. No difference was identified in self-reported pain scores or lengths of hospital stay. Discussion: The addition of LB did not significantly reduce narcotic consumption in patients undergoing TKA, while the cost of LB is prohibitive and should be considered an area of potential cost savings by surgeons and hospitals. The minor reduction in narcotic use in patients undergoing THA likely lacks clinical significance.